2002
DOI: 10.1076/chin.8.4.296.13505
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Parental Report on the BRIEF and Performance-Based Measures of Executive Function in Children with Moderate to Severe Traumatic Brain Injury

Abstract: The Behavior Rating Inventory of Executive Function (BRIEF) is a questionnaire that assesses parental observations of behaviors associated with executive function in children in the home environment. The current investigation examines the relationship between the BRIEF and individually-administered neuropsychological tests in children with traumatic brain injury. Forty-eight children with moderate to severe traumatic brain injury were administered the WISC-III and several performance-based tests of executive f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
129
2
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(157 citation statements)
references
References 10 publications
21
129
2
5
Order By: Relevance
“…Although counterintuitive, these cognitive tests were not designed to measure EF as reflected by everyday behavior. Our findings are consistent with prior work in other clinical populations (Gioia & Isquith, 2004,Mahone et al, 2002,Vriezen & Pigott, 2002, as these studies have demonstrated that deficits on performance-based measures of EF are not correlated with BRIEF ratings of behavioral dysfunction.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Although counterintuitive, these cognitive tests were not designed to measure EF as reflected by everyday behavior. Our findings are consistent with prior work in other clinical populations (Gioia & Isquith, 2004,Mahone et al, 2002,Vriezen & Pigott, 2002, as these studies have demonstrated that deficits on performance-based measures of EF are not correlated with BRIEF ratings of behavioral dysfunction.…”
Section: Discussionsupporting
confidence: 92%
“…It has been suggested that the BRIEF provides an ecologically valid assessment of a child's behavior as it relates to EF, and is therefore more useful in predicting performance in activities of daily living. Furthermore, it has been proposed that the BRIEF may be more sensitive to certain types of executive deficits in children and adolescents that are not well captured by performance-based measures administered in a structured environment (Gioia & Isquith, 2004,Mahone et al, 2002,Vriezen & Pigott, 2002. The BRIEF may prove helpful in treatment planning that is focused on improving performance in individuals' real-world functioning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has demonstrated low correlations between cognitive and behavioural measures of executive functioning among children with early-treated hydrocephalus and focal frontal-lobe lesions 35 and traumatic brain injury. 35,36 Differences in cognitive executive functioning were found to mediate the effects of group differences on the SDQ conduct and hyperactivity subscales. Again, this was the case when comparing the left-sided unilateral CP group with the CTD, and the right-sided unilateral CP group with the CTD.…”
Section: Discussionmentioning
confidence: 99%
“…The Behavior Rating Inventory of Executive Function (BRIEF) 10 was developed as a standardized parent-rated measure intended to assess eight domains of EF. The BRIEF has been used to assess EF in several pediatric samples, including traumatic brain injury, 11,12 attention-deficit-hyperactivity disorder (ADHD), 13 hydrocephalus, 14 and autism. 15,16 The BRIEF differs from other parent and teacher report measures, such as the Achenbach Child Behavior Checklist (CBCL) which is a frequently used parent-report measure of both broad (e.g.…”
mentioning
confidence: 99%